FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT TERHADAP EARLY WARNING SYSTEM SAAT MELINTAS DI PERLINTASAN SEBIDANG TANPA PALANG PINTU - Nurmeindah Pujindasiwi; Arinda Leliana; Muhardono (Jurnal Teknik Sipil dan Arsitektur, 2023)
Improving safety at railroad level crossings is continually conducted to reduce accidents rate at railroad level crossings, especially unguarded official railroad level crossings where accidents often occur. Railroad level crossings are prone to accidents and it mainly caused by accidents that occur at level crossings. Accidents at level crossing are caused by several factors such as human error, crossing guards who are late to lower the barrier, and inferior public awareness to comply with signs at level crossings. This research is located at the railroad level crossing KM 31+988 in Taman District, Sidoarjo. The analysis result shows that the influence factors of people violating the train early warning system are the frequency of random crossings in a day which affects the committing violations with a probability value of 60.72%, and the waiting time before a train passes which takes too long promote committing violations with a probability value of 32 .7%.